2023
DOI: 10.1055/s-0043-1760720
|View full text |Cite
|
Sign up to set email alerts
|

Role of CBCT in Prediction of Oro-antral Communication Post Third Molar Extraction: A Retrospective Study

Abstract: Objective Oro-antral communication (OAC) is one of the most frequently encountered complications during third molar extraction. Various radiographic factors, like excessive maxillary sinus pneumatization, long periods of edentulism, periapical lesions, etc., have been considered high-risk factors for OAC. However, a panoramic radiograph has not proven to be accurate in predicting the chances of OAC. Through this retrospective study, we evaluated the efficacy of a CBCT in predicting the incidence of OAC after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Jung & Cho reported that, contrary to the appearance of wisdom tooth roots projecting into the sinus on panoramic radiographs, CBCT scans showed that the sinus oor is often located buccally to the roots, mimicking root projection on panoramic images [16]. he risk of OAC during upper wisdom tooth removal has been examined in detail by several studies [17,[19][20][21][22], both panoramic radiographs and CBCTs were evaluated, along with clinical parameters. Iwata et al concluded that the usefulness of CT evaluation as an adjunct to panoramic radiographs in predicting OAC following upper wisdom tooth removal is limited [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jung & Cho reported that, contrary to the appearance of wisdom tooth roots projecting into the sinus on panoramic radiographs, CBCT scans showed that the sinus oor is often located buccally to the roots, mimicking root projection on panoramic images [16]. he risk of OAC during upper wisdom tooth removal has been examined in detail by several studies [17,[19][20][21][22], both panoramic radiographs and CBCTs were evaluated, along with clinical parameters. Iwata et al concluded that the usefulness of CT evaluation as an adjunct to panoramic radiographs in predicting OAC following upper wisdom tooth removal is limited [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies do not provide clinical guidance. Potential risk factors of OAC were examined most broadly in relation to upper wisdom tooth removal [17,[19][20][21][22] and mostly reported the superiority of CBCT analysis over panoramic radiographs in the prediction. While cone beam computed tomography (CBCT) has been shown to provide valuable insights into these anatomical considerations, panoramic radiographs remain a more commonly selected diagnostic tool due to their lower cost and reduced radiation exposure.…”
Section: Introductionmentioning
confidence: 99%